(untitled) - Cobb, Nabcy J. (Mountain View, CA., 2001)
This outstanding text blends a strong research base with especially clear and engaging writing. One of the leading authors in the field, Nancy Cobb brings the same scholarship and style that distinguish her Adolescence text to The Child. Self-contained chapters maximize teaching flexibility, supporting either a chronological or topical approach; strong pedagogical features include chapter narratives, overviews and summaries, stop and think questions, and boxes highlighting research and social policy. Online resources include a student learning center with practice quizzes, links to related topical material, and much more. This text is also available in a version covering only infancy and childhood.
Keywords: Child psychology,Child development